Correlation Between Secondary Metabolites of Leaf and the Resistance to Leaf Rust (Hemileia vastatrix) on Several Arabica Coffee Clones - Gatot Subroto; Dwi Erwin Kusbianto; Sholeh Avivi; Slameto Slameto; Setiyono Setiyono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Indicator of coffee resistance to leaf rust attack (Hemileia vastatrix) is needed to select superior coffee plants resistant to biotic stress. This study aims to find the relationship between the content of secondary metabolites and the intensity of leaf rust attack, so that it becomes a reference in the selection of future coffee plants. The experimental design used was a completely randomized design (CRD) with several coffee clones as a treatment. This test tested 5 Arabica coffee clones consisting of Komasti, Maragogik, Usda, Andong sari, and HDT clones. Each consists of 3 replications, and each replication consists of 2 sample plants. Observations were made by observing the intensity of the attack, and plant metabolites such as phenolic content, flavonoids and antioxidant activity were observed when the leaves had been attacked by Hemileia vastatrix. Correlation of leaf rust attack levels with phenolic content, flavonoids and antioxidant activity showed a relationship between each observation variable. Flavonoid content in certain conditions can be used as an indicator to get Arabica coffee plants that are resistant to the attack of leaf rust.